Estrategias lúdico metodológicas para la enseñanza aprendizaje en niños de 7 a 8 años de edad de la Institución Educativa San Francisco de Asís de San Bernardo del Viento - Córdoba (2021)
Music is important that we should not exclude ourselves from giving ourselves the opportunity to know it and not only that, but also to be able to read and write, but it is fundamental that our children, the new generation that rises has as a legacy the importance that is the music and the different ways of learning it. Pedagogy and didactics are the means I have used to achieve a good result in children.